THE EFFECT OF REVERSE FLOTATION METHOD ON SILICA SAND AS WATERPROOFING MORTAR - Okky Putri Prastuti; Ayu Tri Septianingrum; Elisya Dianty Fatmala; Ufafa Anggarini; Tri Eddy Susanto; Nuvixca Dewi Milangsari (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
THE EFFECT OF REVERSE FLOTATION METHOD ON SILICA SAND AS WATERPROOFING MORTAR. Waterproof fabrication mortar cement by silica sand using reverse flotation silica (RFS) method was evaluated by waterproof absorption coefficient, compressive strength test, attractive test, and contact angle. RFS is used to replace waterproof agent and aggregate mortar to reduce cost. The aims of this experiment are to know the RFS process, the ratio between waterproof mortar cement with RFS and mortar, to determine performance and characteristic waterproof mortar cement. Methods used are prepared RFS, mortar cement fabrication, and testing (compressive strength, tensile strength, permeability, contact angle, XRF, FTIR, SEM, BET). Variable used are ratio cement/silica sand, concentrations of CaCl2, curing time, oleic acid, and sodium oleate addition. Optimum collector addition is obtained by oleic acid with compress strength 167.65 kg/cm2, tensile strength 0.16 MPa, permeability 4.6 cm, and contact angle 95°. Curing inside water effect and outside temperature give compress strength 167.65 kg/cm2 and 163.24 kg/cm2, permeability curing inside the water and outside temperature are 4.6 cm and 12 cm. Optimum CaCl2 addition is gained at CaCl2 1.8M with compress strength 64.29 kg/cm2, tensile strength 0.15 MPa, permeability 2.4 cm, contact angle 95°. Optimum ratio cement/RFS is 1:1 with compress strength 167.65 kg/cm2, tensile strength 0.16 MPa, permeability 4.6 cm, and contact angle 950.